Service-Learning, Movies, and Infectious Diseases: Implementation of an Active Educational Program in Microbiology as a Tool for Engagement in Social Justice - Linares, M.; López-Ejeda, N.; Álvarez, P.; Culebras, E.; Díaz, E.; García, M.T.; Majano, C.; Morales, M. L.; Rodríguez-García, A.; Rodríguez-Avial, I.; Utrilla, C. L.; Valenzuela, M.V.; et al. (Frontiers in Microbiology, 2021)
Service-Learning is an educational methodology allows student learning while addressing community needs. A program in microbiology and infectious diseases was implemented in Universidad Complutense de Madrid, Spain. University lecturers, clinical microbiologists, doctorate students and undergraduates from several Bachelor Degrees and courses worked in an interdisciplinary team along with social institutions that attend disadvantaged persons. Using commercial movies that deal with infectious diseases, the students learn clinical microbiology, prepare divulgation materials, visit social centres to accompany and help others to know about illnesses and prevention. The program was developed through two academic years and involved 58 voluntary students, 13 teachers and tutors and 4 social entities as community partners. Postsurvey evaluation of the program revealed a highly satisfactory achievement of goals: acquiring scientific and personal competencies by university students, including critical analysis, science diffusion, solving problems or collaborative team working, and contributing, together with the tutors, to the social responsibility of the university.